2019
DOI: 10.1136/bmjopen-2018-025314
|View full text |Cite
|
Sign up to set email alerts
|

Association between measured teamwork and medical errors: an observational study of prehospital care in the USA

Abstract: ObjectivesThe goal of this study was to examine the relationship between measured teamwork and adverse safety events in the prehospital emergency care of children using high-fidelity simulation. We posit that non-technical skills such as leadership, teamwork, situation awareness and decision-making are associated with the clinical success of teams.DesignObservational study.SettingEmergency medical services (EMS) responders were recruited from public fire and private transport agencies in Oregon State to partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 26 publications
3
46
0
1
Order By: Relevance
“…Previous studies also demonstrated that nursing teamwork significantly impacted missed nursing care (Chapman, Rahman, Courtney, & Chalmers, 2017, Kalisch and Lee, 2010). A data‐based investigation of pre‐hospital care in the USA reported that general teamwork among care delivery teams had a strong association with the risk of severe AEs in the simulation of scenarios in caring for youngsters with critical illnesses and injuries (Herzberg et al, 2019). A study conducted in Iraq found significantly decreased rates of communication‐related errors, medication and transfusion errors, and needle stick incidents following teamwork training (Deering et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies also demonstrated that nursing teamwork significantly impacted missed nursing care (Chapman, Rahman, Courtney, & Chalmers, 2017, Kalisch and Lee, 2010). A data‐based investigation of pre‐hospital care in the USA reported that general teamwork among care delivery teams had a strong association with the risk of severe AEs in the simulation of scenarios in caring for youngsters with critical illnesses and injuries (Herzberg et al, 2019). A study conducted in Iraq found significantly decreased rates of communication‐related errors, medication and transfusion errors, and needle stick incidents following teamwork training (Deering et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Non‐technical skills (e.g. good communication and teamwork) play a crucial role in preventing AEs and in ensuring patient safety (Herzberg et al, 2019). In the past decade, the growing complexity of health care systems has led to an emphasis on the need for teamwork in health care practice to improve quality care and it has been understood to be a key factor that contributes to reductions in AEs (Manser, 2009, Hwang and Park, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Effective teamwork in healthcare not only augments patient's satisfaction but also decreases burnout among the health professionals. [1][2][3][4] The Agency for Healthcare Research and Quality (AHRQ), the Joint Commission and other institutions ranked teamwork as a dominant factor for enhancing the healthcare quality. 5 6 Furthermore, teamwork has been classified as an important competency to help optimise the healthcare services and poor teamwork could increase the medical errors and reduce patient safety.…”
Section: Introductionmentioning
confidence: 99%
“…Materializing, in a study that examined the relationship between medical team work and adverse safety events in pre-hospital emergency care for children using high-fidelity simulation, at least one error was found in 82% of the simulations [18]. Distinguishing the physician's guilt is an arduous task and by way of example Campo et al [19] found that a patient in an intensive care unit receives an average of 178 interventions per day and the risk of error or adverse event increases by 6% each day of hospitalization. If a medical error occurs, who is directly responsible?…”
Section: Discussionmentioning
confidence: 99%